Ética utilitária e justiça em John Rawls: liberdade e garantia dos direitos individuais como um problema de filosofia prática - Melo, Damião Benilson Gomes de (2020)
In times of instability of political institutions, the serious violation of the right to freedom becomes an invitation of this research to the analysis of the theory of ―justice as fairness‖ by American jurist and philosopher John Bordley Rawls (1921-2002) and the tools it offers us for a standard of justice. The main thrust of the theory is the author‘s criticism of the restrictions imposed by utilitarian ethics on the freedom of the individual, provoked by the maximizing principle of general happiness at the expense of the particular will. This principle, which guided classical utilitarianism, was defended by Jeremy Bentham (1748-1832) and perfected by John Stuart Mill (1806-1873), until it reached the hands of Henry Sidgwick (1838-1900). Our investigation is based on a comparative premise. We will verify whether the application of the principles of Rawlsian theory of justice offers a better answer to the problem of justice verified in utilitarian doctrine. We intend to examine their ability to determine when institutions and individuals will be just by a scheme of social cooperation. To investigate whether the theory can guarantee, protect, and enforce basic rights and fundamental freedoms. Descriptively evaluate their arguments and, finally, answer whether ―justice as fairness‖ can be embraced as a practical alternative superior to utilitarianism, with a view to achieving justice and substantial rights. Our hypothesis is negative and is due to the allegory that the author presents from the beginning for his conception of justice. This does not prevent the recognition of the author‘s contributions to the reflections on public policies and constitutional democracy itself.